Detection of transgressive segregants for quantitative characters in F3 generation of in-ovulo cultured interspecific triple cross of cotton viz; colchicide (G. arboreum x G. anomalum) x G. barbandense - Hingane, Anupama; Mehetre, S.S. (Annals of Agricultural Research, 2014)
In the present investigation, the F3 segregating generations of interspecific triple cross between colchicide (G. arboreum x G. anomalum) x G. barbandense were evaluated with an objective to detect transgressive segregants for quantitative characters. Very high numbers of transgressive segregants were observed in F3 generation of interspecific triple cross for nine yield contributing characters. Looking towards the range of variation for yield and yield contributing characters it appears that very high amount of variability has been created among the progenies. The vast variation in transgressents also suggested the possibility of combining desirable genes from all the three species together. In most of the segregants in F3 generation, seed cotton yield of better parent was found to be transgressed simultaneously with transgression of one or more other characters. The most promising transgressive segregants observed in F3 generation also had higher intensity of expression than the increasing parent for one or more characters. These entries need to be evaluated for their performance vis-a-vis their hybrids and commercial hybrids. On the basis of observed high values of trangressive segregants, it can be concluded that, when desired intensity of character is not available in the parents, transgressive breeding may be successfully used to extend the limit of expression of a particular character.